The Curriculum of ELT Education in Indonesian and Vietnamese Universities: A Comparison Study - Zohri Hamdani; Balqis Husain (Institut Agama Islam Negeri Palopo, 2023)
Both Indonesia and Vietnam provide English as foreign language instruction. In contrast to Indonesia, where English proficiency is low, Vietnam has a moderate level of English proficiency. Although Vietnam has a moderate level of English proficiency, its curriculum is nearly identical to that of Indonesia, making it suitable for comparative research. This research aimed to identify the significant differences between Indonesian and Vietnamese universities’ English language teacher education curricula. This study employed a qualitative methodology to compare the English as a foreign language teacher education curricula in Vietnam and Indonesia. In this study, descriptive analysis was utilized. The English education curricula documents obtained from the university’s website were used for data analysis. The research settings were Universitas Pasifik Morotai in Indonesia and the Giao Su-IESUS Evangelical School of Universal Studies in Vietnam. The finding showed that Vietnamese Universities stressed the dimension of content knowledge, communication competence, contextual knowledge, and professionalism practice theory. However, teaching competence, research knowledge, Community Practice Membership, and general knowledge are often overlooked. Compared to the EFL curriculum in Vietnam, the Indonesian curriculum, particularly at Universitas Paisfik Morotai, emphasized communication skills, content knowledge, research knowledge, and teaching competence/pedagogical aspects